2005
DOI: 10.1038/sj.onc.1208542
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of bovine papillomavirus type 1 E6 and E7 genes on Fas-mediated apoptosis

Abstract: Programmed cell death (PCD), best exemplified by apoptosis, is a genetically programmed process of cellular destruction that is indispensable for normal development and homeostasis of multicellular organisms. Tumor necrosis factor a (TNF) and related cytokines are employed by host defenses to eliminate virally infected cells through induction of apoptosis. Many viruses have evolved specific gene products to modulate this process. We have recently shown that the bovine papillomavirus type 1 (BPV-1) E6 and E7 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 82 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…However, some studies have demonstrated relationships between other E genes and apoptosis (16). To the best of our knowledge, previous reports have not mentioned bilateral trends in E gene expression with respect to progression and regression.…”
Section: Tab 4 Percentage (%) Of All Reactions Belonging To Immunohmentioning
confidence: 79%
See 1 more Smart Citation
“…However, some studies have demonstrated relationships between other E genes and apoptosis (16). To the best of our knowledge, previous reports have not mentioned bilateral trends in E gene expression with respect to progression and regression.…”
Section: Tab 4 Percentage (%) Of All Reactions Belonging To Immunohmentioning
confidence: 79%
“…Accordingly, E5 expression is believed to play a role in promoting the growth of all tumor components from deep to surface layers. BPV-1 encodes E6 oncoproteins excepting E2 and E5 are the major transforming protein interacting with each other (16,21). E6 is another crucial factor in this transformation.…”
Section: Tab 4 Percentage (%) Of All Reactions Belonging To Immunohmentioning
confidence: 99%
“…This action promotes the p53 degradation [13,21,79,83]. Additionaly, the HPV-5 and 8 E6 oncoproteins interact with the CBP/ p300 complex [84][85][86], causing the TP53 downregulation by epigenetic mechanisms [87]. Furthermore, the E6 oncoprotein can interact with XRCC1 and O 6 -methylguanosine-DNA-methyltransferase proteins, which are recruited during the single-strand DNA break (SSB) repair [35], leading to cytogenetic damages [35] and neosis [88].…”
Section: Oncoproteins Codified By Early Region (E5 E6 and E7)mentioning
confidence: 99%
“…, 2005; Liu and Baleja, 2008), which directs the p53 to 26S proteasome (Cai et al , 2013). The HPV-5 and 8 as well as BPV E6 oncoprotein interact with the CBP/p300 complex (Werness et al , 1990; Zimmermann et al , 2000; Liu et al , 2005), promoting p53 downregulation (Zimmermann et al , 1999). The loss of p53 contributes to genomic instability verified in cells infected by PVs (Araldi et al , 2013, 2015b), as well as in cells treated with BPV-1 E6 recombinant oncoprotein (Araldi et al , 2015a).…”
Section: Oncogenic Proteins Expressed By Pvs: E5 E6 and E7mentioning
confidence: 99%
“…However, only BPV was able to infect the species (Koller and Olson, 1972). Due to its capability to infect different species and the pathogenic and morphological characteristics shared with HPV (Munday, 2014), BPV has been used as a prototype to study PV biology and oncology (Koller and Olson, 1972; Campo, 2002; Liu et al , 2005; Campo, 2006; Costa and Medeiros, 2014). Therefore, research involving BPV has contributed with the understanding of viral oncogenesis (Costa and Medeiros, 2014; Munday, 2014).…”
Section: Bpv As a Model For Hpvmentioning
confidence: 99%